Odpowiedzi

2010-04-11T20:39:51+02:00
A) 3x - 2x = 4+5
x=9
b) -5x + 9x = 3+17
x = 5
c) -5x + 2 x = -8-10
x=6
  • Użytkownik Zadane
2010-04-11T20:41:00+02:00
A) 3X-5=4+2x
B)-5X-17 =-9x+3
c)-5x+10=-2x-8
d)7x+14=5x-22
e)2x-4+5x=x+2
f) -3+2x -6 =3-4x
g)7x+2=5+3x+9
h)-5x +12+x=2x-12


a. 3x-2x=4+5
x=9

b. -5x+9x=3+17
-4x=20
x=-5


c.-5x+2x=-8-10
-3x=-18
x=6


d. 7x-5x=-22-14
2x=-36
x=-18

e. 6x=6
x=1

f.-12=-6x
x=2

g.7x-3x=5+9-2
4x=12
x=3

h. -5x +12+x=2x-12
-4x-2x=0
x=0
Najlepsza Odpowiedź!
2010-04-11T20:51:15+02:00
A) 3X-5=4+2x
3x-2x = 5+4
x=9
B)-5X-17 =-9x+3
-5x+9x=3+17
4x=20 /:4
x=5
c)-5x+10=-2x-8
-5x+2x=-8-10
-3x=-18/:(-3)
x=6
d)7x+14=5x-22
7x-5x=-22-14
2x=-36/:2
x=-18
e)2x-4+5x=x+2
2x+5x-x=2+4
6x=6/:6
x=1
f) -3+2x -6 =3-4x
2x+4x=3+3+6
6x=12/:6
x=6
g)7x+2=5+3x+9
7x-3x=5+9-2
4x=12/:4
x=3
h)-5x +12+x=2x-12
-5x+x-2x=-12-12
-6x=-24/:(-6)
x=4

a)2x-(1-4x)=2+(8x-5)
2x-1+4x=2+8x-5
2x+4x-8x=2-5+1
-2x=-2/:(-2)
x=1
b)4-2(5-x)=x-4(x-1)
4-10+2x=x-4x +4
2x-x+4x=4-4+10
5x=10/:5
x=2
c)7-(3x+4)=(x+1)-(2x+4)
7-3x-4=x+1-2x-4
-3x-x+2x=1-4-7+4
-2x=-6/:(-2)
x=3
d)x+3-(4-x)=3x-(2x-3
x+3-4+x=3x-2x+3
x+x-3x+2x=3-3+4
x=4